Relationship Between Mothers Who Did Pregnancy Exercise And The Occurrence of Birth Canal Laceration At The Time Of Delivery - Rosmala Kurnia Dewi; sri untari (LPPM AN NUUR, 2021)
Background: Perineal laceration is one of the causes of bleeding that results in death. Preliminary study result in the Geyer I Puskesmas in January to March 2019, out of 120 maternity mothers there were 104 maternal births who had road lacerations born of a total of 120 with a degree 1 of 46 maternity, degrees 2 as many as 48, degrees 3 maternity mothers as many as 0, degrees 4 maternity mothers as many as 0 and mother who did not experienci laceration as many as 16 mothers, one of the alternative methods to reduce laceration. Births performed during labor include (pregnancy of kegel) exercises. Serves to strengthen the pelvic floor muscles. Objective: The aim of this study was to determine the relationship between mothers who did pregnancy exercise and the occurrence of birth canal laceration at the time of delivery. Methods: Retrospective analytical design. The population in this study was the number of all physiological maternity mothers at Geyer I Health Center in Grobogan Regency. The technique for taking samples using the total sampling technique. Correlation test using spearman contingency coefficient. The respondents obtained from this study were 120 physiological maternity mothers. Results: 120 respondents who gave birth to 16 mothers without birth lacerations, 46 had birth lacerations of the 1st degree, 58 had birth lacerations in the second and 48 degrees following pregnancy exercises ≥3 times, 72 pregnant women participated in pregnancy exercises <3. From the results of the study, Ho was rejected because it was shown by the p value of 0.005 <0.05 or 95% confidence level, the strength of the correlation was 0.256 and it could be concluded that there was a relationship between the participation of pregnant gymnastics and the birth canal laceration. Conclusion: From the results of this study it was found that mothers aged <20 years and> 30 were at risk of experiencing birth canal lacerations because reproduction was not ready and rigid pelvic floor muscles to overcome it were carried out actively in conducting pregnancy exercises routinely because pregnant women taking gymnastics pregnant ≥3 chance of not having birth lacerations at the time of delivery